Basic aspects and properties of biopolymers - N. F., Mazuki; Saadiah, Mohd Ali; A. F., Fuzlin; N. M., Khan; Ahmad Salihin, Samsudin (Royal Society of Chemistry, 2022)
The consumption of nutritious foods is claimed to confer health benefits and wellness to human beings. The increasing awareness about nutritional needs and health benefits has attracted the attention of researchers, food and drug producers, distributors, health care professionals, and consumers in designing nutraceuticals and functional food products. However, these nutraceuticals and functional food products are hampered by chemical instability, limited solubility in an aqueous medium, and experience fast metabolism that could lead to poor oral bioavailability. These limitations could be overcome by using appropriate biopolymers and assembly methods to encapsulate the bioactive compounds and help to protect the nutraceuticals and functional food products from undesired interactions. Therefore, various attempts have been explored to apply different sources and types of biopolymers as potent ingredients due to their remarkable therapeutic potential. The manufacture and design of these biopolymers must be done in a careful manner to achieve the final products’ desired functional attributes. Researchers must try to meet the requirements of specific basic properties such as physicochemical stability, functional and structural properties, optical and rheological properties, encapsulation, and release properties. Herein, this chapter provides a comprehensive discussion on the design and fabrication of functional biopolymers as a potent substitute in the production of functional food products and nutraceuticals.